Strategi Live Tiktok dalam Mengatasi Fluktuasi Penonton Melalui Optimalisasi Interaksi Menit Awal - Naura Natasya Putri; Nuruni Ika Kusuma Wardhani (Masyarakat Ekonomi Syariah Bogor, 2026)
The live streaming feature has become a crucial instrument in digital marketing communication for local products, but live host teams frequently face extreme fluctuations in concurrent viewer counts. This community service program aims to analyze the underlying factors causing viewer disparities and formulate tactical streaming strategies for the Papagrey business unit at CV. Avero Indonesia. The implementation method utilized a practical mentoring and action research approach, analyzing and comparing metric logs from two TikTok LIVE sessions lasting ±1.5 hours extracted from the official partner account's Live Center. The evaluation results indicated that Session A (standard cat content) experienced poor performance, capturing only 488 cumulative viewers due to monotonous materials (introducing cat breeds, daily feeding formulas, basic Q&A care sessions, and general introductions to Glowking supplements) compounded by strict non-yellow basket transaction regulations. Conversely, Session B (live direct-action education) triggered a massive algorithmic distribution boost, peaking at over 6,000 concurrent viewers by optimizing immediate high-intensity visual attractiveness (visual hook) through live broadcasts of direct physical handling, including cat grooming, cat mating processes, or real-time cat birthing events during the critical Golden Minutes phase. The practical implication of this program requires host operational re-engineering to actively incorporate high-engagement animal displays to maintain consistent audience retention.